New Public Management in the public sector in Canada: The contribution, adoption and involvement of Internal Audit - Dutta, Somen (Université d'Ottawa | University of Ottawa, 2020)
In today’s world, many governments are interested in modernizing their public service, leading them to introduce new techniques and tools of management inspired by the private sector. This new field is called the New Public Management. The quality and the efficiency of public services constitutes a priority for the government. Like many other functions within public sector, New Public Management had also a profound impact on the scale and scope of internal audit function. This study aims to investigate the contribution, adoption and the involvement of internal audit in improving the management of public sector in Canada. The result shows that internal auditing contributes by adding value to federal departments in two main ways: (i) it provides comfort and reassurance to the senior management and the audit committees (ii) it promotes organizational learning on how to improve management controls, governance processes and risk management and advisory services beneficial to executives involved in operations. In addition, the internal audit function is well situated within departments to help them become more innovative. From internal document reviews, it was found that the internal audit function is well positioned within the department’s body and complies completely with the standards of Institute of Internal Auditors (IIA) and the Treasury Board Internal Audit policy. This paper also analyzes how the involvement of internal audit as a tool of accountability changes with the change in Government in Canada. The result shows that there is a negative association between a Liberal Party government and the number of internal audit reports, i.e. as we move from Conservative party government to Liberal party government, the federal departments conduct less internal audits. Keywords: New Public Management, internal audit, governance, risk management, performance measurement, government of Canada, federal departments